Impact of Laser Guide Star facilities on neighbouring telescopes: the case of GTC, TMT, VLT, and ELT lasers and the Cherenkov Telescope Array. Issue 1 (9th August 2018) - Gaug, M; Doro, M
ABSTRACT: Powerful Laser Guide Star (LGS) systems are standard for the next generation of extremely large telescopes. However, modern earth-based astronomy has gone through a process of concentration on few sites with exceptional sky quality, resulting in those becoming more and more crowded. The future LGS systems encounter hence an environment of surrounding astronomical installations, some of which observing with large fields of view. We derive formulae to calculate the impact of LGS light on the camera of a neighbouring telescope and the probabilities for a laser crossing the camera field of view to occur, and apply these to the specific case of the next very high energy gamma-ray observatory 'Cherenkov Telescope Array' (CTA). Its southern part shall be constructed in a valley of the Cerro Armazones, Chile, close to the 'Very Large Telescope' and the 'European Extremely Large Telescope' (ELT), while its northern part will be located at the 'Observatorio del Roque de los Muchachos', on the Canary Island of La Palma, which also hosts the 'Gran Telescopio de Canarias' (GTC) and serves as an optional site for the 'Thirty Meter Telescope' (TMT), both employing LGS systems. Although finding the artificial star in the field of view of a CTA telescope will not disturb observations considerably, the laser beam crossing the field of view of a CTA telescope may be critical. We find no conflict expected for the ELT lasers, however, 1 per cent (3 per cent) of extra-galactic and 1 per cent (5 per cent) of galactic observations with the CTA may be affected by the GTC (TMT) LGS lasers, unless an enhanced version of a laser tracking control system gets implemented.